Experience of entecavir in renal graft recipients with chronic hepatitis B - M. L. Zubkin; Ye. P. Sel'kova; F. K. Kokoyeva; T. A. Semenenko; V. I. Chervinko; A. N. Kolomoyets; E. M. Balakirev; A. V. Frolov; T. P. Nekrasova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate efficacy and safety of entecavir (ETV) in chronic hepatitis B (CHB) at renal graft recipients (RGR).Material and methods. Four RGR with CHB on in mean 71,5±36,9 month after kidney transplantation received treatment by entecavir. In 2 patients with CHB biochemical remission on background of previous lamivudine (LAM) treatment, who developed YVDD mutation ETV dose was 1 mg/day. One of them was HBeAgnegative prior to onset of LAM treatment, and the other developed HBeAg seroconversion while being at LAM treatment. The viral load before prescription of entecavir at these patients was 1,6×103 and 3,9×104 copies/ml respectively. Two other «naive» RGR with HBeAg-positive CHB, that were infected by HCV as well, received 0,5 mg/ day of entecavir. Activity of ALT was 98 and 149 IU/l, HBV viral load – 1,6×109 and 1,0×108 copies/ml. In all patients stage 1of fibrosis by METAVIR scale was determined. Calculated glomerular filtration rate was over 60 ml/min.Results. Duration of ETV treatment in 2 RGR (that previously received LAM) with normal ALT level and low viral load was 13 and 23 months. In 6 months after treatment onset HBV DNA was not determined in blood of these patients. Duration of ETV treatment at «naive» patients was 26 and 24 months. Biochemical remission developed in 10 and 15 months after the start treatment. The viral load steadily dropped and HBV DNA elimination has been achieved in 25 and 23 months respectively. One of these patients had HBeAg seroconversion. During treatment no undesirable effects were marked. Function of renal graft remained stable in 3 patients and decreased in one case patient after development of acute rejection crisis on a background of decrease of dose of immune suppressants.Conclusion. Entecavir demonstrated high effectiveness and safety at limited number of RGR with CHB in short-term course of treatment.